2007
DOI: 10.1111/j.1365-2141.2007.06584.x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed redistribution of CD27, CD40 and CD80 positive B cells and the impaired in vitro immunoglobulin production in patients with non‐Hodgkin lymphoma after rituximab treatment as an adjuvant to autologous stem cell transplantation

Abstract: SummaryRecent studies have indicated that patients who received rituximab as an adjuvant to stem cell transplantation (SCT) demonstrated an increased risk of developing severe hypogammaglobulinaemia, which was found to be a result of delayed recovery of CD27 positive memory B cells and impaired isotype expression. It appears that rituximab influences both the quantity and quality of B-cell redistribution. Precisely how the B-cell repertoire regenerates after anti-CD20-mediated transient B-cell depletion in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 19 publications
1
23
1
Order By: Relevance
“…It has been shown in various diseases, including SLE (31) and non-Hodgkin's lymphoma (40). The reduced mutational rate of IgDϩ memory B cells after rituximab treatment does not seem to be related to RA or ongoing methotrexate therapy, since we observed the same pattern of few or no mutations 1 year after rituximab treatment in a patient with SLE who had received no additional immunosuppressive treatment (data not shown).…”
Section: Discussionsupporting
confidence: 74%
“…It has been shown in various diseases, including SLE (31) and non-Hodgkin's lymphoma (40). The reduced mutational rate of IgDϩ memory B cells after rituximab treatment does not seem to be related to RA or ongoing methotrexate therapy, since we observed the same pattern of few or no mutations 1 year after rituximab treatment in a patient with SLE who had received no additional immunosuppressive treatment (data not shown).…”
Section: Discussionsupporting
confidence: 74%
“…12 Lymphoma patients who receive rituximab as adjuvant or maintenance following autologous HSCT, however, have been reported to have an increased risk of developing severe and long-lasting hypogammaglobulinemia despite quantitative CD19 þ B-lymphocyte recovery. [20][21][22][23] Laboratory studies in patients with lymphoma or alloantibodies before kidney transplantation have shown a delayed recovery of CD19 þ /CD27 þ B-memory cells and impaired isotype expression following rituximab therapy as seen in patients with common variable immunodeficiency, suggesting that rituximab can affect not only B-cell quantities but also the recovery of functional B-cell repertoires and differentiation into plasma cells. 20,21,24,25 Little is known of the consequences of rituximab therapy on B-lymphocyte depletion and recovery in patients with PTLD following allogeneic HSCT, particular in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23] Laboratory studies in patients with lymphoma or alloantibodies before kidney transplantation have shown a delayed recovery of CD19 þ /CD27 þ B-memory cells and impaired isotype expression following rituximab therapy as seen in patients with common variable immunodeficiency, suggesting that rituximab can affect not only B-cell quantities but also the recovery of functional B-cell repertoires and differentiation into plasma cells. 20,21,24,25 Little is known of the consequences of rituximab therapy on B-lymphocyte depletion and recovery in patients with PTLD following allogeneic HSCT, particular in pediatric patients. Although incubation of B cells with anti-CD20 antibody depletes normal circulating B cells and has variable effects on cell cycle progression and signaling, the detailed biologic functions of CD20 remain uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study analyzed B-cell sub-populations in 17 lymphoma patients, 12-43 months after the last dose of rituximab. 10 They demonstrated a delayed recovery of memory B cells, a defect in expression of co-stimulatory molecules and impaired immunoglobulin production in vitro. With this report, we wish to increase physician awareness of impaired immune reconstitution of the B-cell compartment and associated possible infections in HSCT patients receiving lymphocytotoxic chemotherapies including rituximab.…”
mentioning
confidence: 99%